Human Ecology and Adaptive Governance in Vulnerable Mangrove Ecosystems: Global Trends and Implications for Indonesia - Riesti Triyanti; Tri Retnaningsih Soeprobowati; Sri Sumiyati; Nur Arifatul Ulya (Balai Besar Riset Sosial Eonomi Kelautan dan Perikanan, 2026)
Mangrove ecosystems are vital for coastal socio-ecological resilience, yet governance outcomes often remain weak due to institutional fragmentation and escalating climate risks. This study combines a PRISMA 2020 systematic review with bibliometric mapping (VOSviewer) of 520 Scopus-indexed publications (2000–2025) to trace global research evolution and derive Indonesia-relevant insights. Publication output accelerated sharply after 2018, peaking at >60 documents in 2024, and research production is concentrated in high-income countries (e.g., the United States 18.6%), while Indonesia contributes only 9.7% despite hosting the world’s largest mangrove extent. Keyword mapping identifies three dominant clusters—ecological foundations, human ecology and governance, and environmental dynamics—with recent trends shifting toward climate–governance and resilience themes. The key gap is that governance and resilience discourse rarely translates into an integrated institutional design linking multi-level coordination, community adaptive capacity, and long-term financing; the novelty of this study is the Dynamic Adaptive Institutional Alignment Framework that explicitly integrates these components to inform Indonesia-oriented governance reform. Findings support moving beyond restoration targets toward adaptive, learning-based, and financially durable governance architectures. The study contributes theoretically by operationalizing adaptive governance within mangrove socio-ecological systems and offers policy guidance for strengthening climate-responsive and inclusive coastal governance under conditions of increasing uncertainty.